LIFESTYLE, MENTAL HEALTH AND POLYCYSTIC OVARIAN SYNDROME (Fiep Bulletin - online, 2025)
Introduction: Polycystic ovary syndrome (PCOS) is one of the most common endocrine disorders in women of reproductive age and has a significant negative impact on mental health, with higher prevalence rates of depression in women with PCOS compared to women without the syndrome. However, the evidence for the effects of exercise and dietary intervention on the mental health of women with PCOS is unclear. Objective: To assess the importance of physical exercise and diet on the mental health of women with PCOS. Methods: A systematic review was conducted following the recommendations and guidelines of the Cochrane Handbook for Systematic Reviews and the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). Results: Seven randomized clinical trials were included, involving 612 women aged 18 to 44 years diagnosed with PCOS based on the Rotterdam criteria. The interventions lasted from 10 weeks to 5 months. Most interventions were based on protein intake, carbohydrate reduction and aerobic exercise. Interventions involving physical exercise alone or combined with diet showed improvements in the mental health of the target population. Conclusion: There is evidence that lifestyle interventions (exercise and diet) can improve mental health in women with PCOS. However, this information should be interpreted with caution due to several included studies having a high risk of bias and small sample sizes. Further research with greater methodological rigor is recommended.
Keywords: Exercise; Health behavior; Dietetics; Polycystic ovary syndrome; Mental health